AWS Observability Handbook Monitor, Trace, and Alert Your Cloud Applications with AWS' Myriad Observability Tools - Lingamallu, Phani Kumar; Oliveira, Fabio Braga de (Packt Publishing, Limited, 2023)
Accelerate cloud adoption using AWS CloudWatch, X-ray, Distro for OpenTelemetry, Amazon DevOps Guru, and more to monitor and build resilient systems Purchase of the print or Kindle book includes a free PDF eBook Key Features Gain a thorough understanding of observability principles along with different AWS service offerings and best practices Ensure customer satisfaction by monitoring user experience and fixing bottlenecks quickly Learn from experts to get the best possible insights into AWS' observability solutions Book Description As modern application architecture grows increasingly complex, identifying potential points of failure and measuring end user satisfaction, in addition to monitoring application availability, is key. This book helps you explore AWS observability tools that provide end-to-end visibility, enabling quick identification of performance bottlenecks in distributed applications. You'll gain a holistic view of monitoring and observability on AWS, starting from observability basics using Amazon CloudWatch and AWS X-Ray to advanced ML-powered tools such as AWS DevOps Guru. As you progress, you'll learn about AWS-managed open source services such as AWS Distro for OpenTelemetry (ADOT) and AWS managed Prometheus, Grafana, and the ELK Stack. You'll implement observability in EC2 instances, containers, Kubernetes, and serverless apps and grasp UX monitoring. With a fair mix of concepts and examples, this book helps you gain hands-on experience in implementing end-to-end AWS observability in your applications and navigating and troubleshooting performance issues with the help of use cases. You'll also learn best practices and guidelines, such as how observability relates to the Well-Architected Framework. By the end of this AWS book, you'll be able to implement observability and monitoring in your apps using AWS' native and managed open source tools in real-world scenarios. What you will learn Capture metrics from an EC2 instance and visualize them on a dashboard Conduct distributed tracing using AWS X-Ray Derive operational metrics and set up alerting using CloudWatch Achieve observability of containerized applications in ECS and EKS Explore the practical implementation of observability for AWS Lambda Observe your applications using Amazon managed Prometheus, Grafana, and OpenSearch services Gain insights into operational data using ML services on AWS Understand the role of observability in the cloud adoption framework Who this book is for This book is for SREs, DevOps and cloud engineers, and developers who are looking to achieve their observability targets using AWS native services and open source managed services on AWS. It will assist solution architects in achieving operational excellence by implementing cloud observability solutions for their workloads. Basic understanding of AWS cloud fundamentals and different AWS cloud services used to run applications such as EC2, container solutions such as ECS, and EKS will be helpful when using this book.